Sex disparities in COVID-19 outcomes of inpatients with diabetes: insights from the CORONADO study. Issue 2 (5th July 2021) - Tramunt, Blandine; Smati, Sarra; Coudol, Sandrine; Wargny, Matthieu; Pichelin, Matthieu; Guyomarch, Béatrice; Al-Salameh, Abdallah; Amadou, Coralie; Barraud, Sara; Bigot, Edith; Bordier, Lyse; Borot, Sophie; et al.
Abstract : Objective: Male sex is one of the determinants of severe coronavirus diseas-e-2019 (COVID-19). We aimed to characterize sex differences in severe outcomes in adults with diabetes hospitalized for COVID-19. Methods: We performed a sex-stratified analysis of clinical and biological features and outcomes (i.e. invasive mechanical ventilation (IMV), death, intensive care unit (ICU) admission and home discharge at day 7 (D7) or day 28 (D28)) in 2380 patients with diabetes hospitalized for COVID-19 and included in the nationwide CORONADO observational study (NCT04324736). Results: The study population was predominantly male (63.5%). After multiple adjustments, female sex was negatively associated with the primary outcome (IMV and/or death, OR: 0.66 (0.49–0.88)), death (OR: 0.49 (0.30–0.79)) and ICU admission (OR: 0.57 (0.43–0.77)) at D7 but only with ICU admission (OR: 0.58 (0.43–0.77)) at D28. Older age and a history of microvascular complications were predictors of death at D28 in both sexes, while chronic obstructive pulmonary disease (COPD) was predictive of death in women only. At admission, C-reactive protein (CRP), aspartate amino transferase (AST) and estimated glomerular filtration rate (eGFR), according to the CKD-EPI formula predicted death in both sexes. Lymphocytopenia was an independent predictor of death in women only, while thrombocytopenia and elevated plasma glucose concentration were predictors of death in men only. Conclusions: In patients with diabetes admitted for COVID-19, female sex was associated with lower incidence of early severe outcomes, but did not influence the overall in-hospital mortality, suggesting that diabetes mitigates the female protection from COVID-19 severity. Sex-associated biological determinants may be useful to optimize COVID-19 prevention and management in women and men.